Charles V and the Fury at the Prado Museum: The Power of the King’s Body as Image - Vagnoni, Mirko (Eikón / Imago, 2017)
This is the text of the presentation “Charles V and the Fury at the Prado Museum: The Power of the King’s Body as Image” at the International Conference “El poder del la imagen en el Museo del Prado” (Madrid, December 12th-13th, 2017). By analysing the bronze sculpture Charles V and the Fury (Leone and Pompeo Leoni, 1549-1564. Prado Museum, Madrid), this paper aims to underline the necessity to study royal images in their context (with particular attention to their visibility) to understand better their social use and function. This type of methodological approach can be without any doubt very useful for the historiography in the overall analysis of the leader’s portrait and can stimulate new researches for the future and reformulate some of the traditional conceptions on this topic.